Stronger dung removal in forests compared with grassland is driven by trait composition and biomass of dung beetles. (9th August 2019) - Buse, Jörn; Entling, Martin H.
Abstract : 1. Ecosystem processes depend on the biomass of the involved organisms, but their functional diversity may play an additional role. In particular, the exclusion of key functional groups through habitat disturbance may lead to the breakdown of ecosystem functions. Dung removal is an important process contributing to nutrient cycling and thus productivity in grazed ecosystems. 2. This study investigated the role of different functional groups of dung beetles in dung removal in different habitats within a wood‐pasture in two different seasons. An experimental setting with 12 blocks and 108 dung pads was used to investigate short‐term dung removal over 1 week of exposure. 3. Dung removal was most strongly affected by habitat type, with almost 40% lower levels in grassland than in adjacent forest and forest gaps. Of all assemblage characteristics, total biomass of tunneller species was the strongest predictor of dung removal, whereas functional diversity showed no significant effect. In accordance with the dung removal pattern at habitat type level, densities of large tunnellers were suppressed in grassland compared with forest. 4. It is concluded that dung removal is habitat‐specific and large tunnellers play a disproportionate role in this important ecosystem function in temperate forests. Abstract : Dung removal is a key ecological function in grazed ecosystems. Short‐term dung removal under field conditions was compared between grassland forest and open patches cut into forest. There were strong differences in dung removal between habitat types, with higher rates observed in forest than in grassland. The results showed that the presence and biomass of tunnellers had a disproportionate positive effect on dung removal in a temperate wood‐pasture.